Clinical relevance of nutraceuticals in hypertension management: mechanisms, efficacy, and integration into therapeutic protocols - Samuel Oluwadare Olalekan; Patrick Godwin Okwute; Ifabunmi Oduyemi Osonuga; Bukunola Oluyemisi Adegbesan; Esther Nkechi Ezima; Idowu Matthew Adeyemi (Bulletin of the National Research Centre, 2025)
Abstract Background Hypertension remains a significant global health burden, affecting over 1.28 billion people worldwide. As a leading risk factor for cardiovascular disease, stroke, and renal failure, effective blood pressure control is essential to reduce morbidity and mortality. Although conventional antihypertensive therapies are effective, their long-term use is often limited by adverse effects and patient non-adherence. This has prompted interest in exploring alternative or adjunctive interventions, particularly those with favorable safety profiles. Results Nutraceuticals, derived from natural food-based sources, have gained increasing attention for their potential role in hypertension management. These agents exert antihypertensive effects through several well-characterized mechanisms. One such mechanism is angiotensin-converting enzyme inhibition, which reduces vasoconstriction and sodium retention. Another is vasodilation mediated by endothelial function, which enhances vascular relaxation and lowers systemic vascular resistance by restoring nitric oxide bioavailability and reducing inflammation. Nutraceuticals also contribute to metabolic regulation by modulating glucose and lipid metabolism, thereby improving insulin sensitivity and reducing cardiovascular risk. Additionally, emerging evidence supports the relevance of nutrigenetics, where genetic profiling can help tailor nutraceutical interventions to individual genotypes, potentially optimizing therapeutic outcomes and enabling more personalized hypertension management. Conclusions This review provides a mechanistic and evidence-based overview of how nutraceuticals may complement conventional antihypertensive therapies. Their integration into clinical practice could enhance blood pressure control, improve patient adherence, and minimize adverse effects. As research advances, especially in the area of personalized nutrition, nutraceuticals may offer a promising pathway toward more individualized and effective hypertension management strategies.